The Impact of Economic Shocks on Global Undernourishment - Tiwari, Sailesh; Zaman, Hassan (2012)
This paper estimates the impact of the 2008 food price spike and the 2009 contraction in global growth on undernourishment rates. The analysis is based on a methodology that uses a calorie-income relationship and income distribution data. The authors find that the 2008 global food price spike may have increased global undernourishment by about 6.8 percent, or 63 million people. Moreover, they show that the sharp slowdown in global growth in 2009 could have contributed to 41 million more undernourished people compared with what would have happened if the economic crisis had not occurred.